Main clinical determinants of the presence of coronary artery disease in patients with left bundle branch block - Hashemi Jazi, Mohammad; Nilforoush, Peyman; Gharipour, Mojgan; Batvandi, Azadeh; Mohammadi, Robabeh; Najafi, Roya (Acta Biomedica Atenei Parmensis, 2015)
Background: Considering clinical parameters as mainpredictors for coronary artery disease (CAD)in patients with left bundle branch block (LBBB) can be very helpful to explain high likelihood of ischemic events in LBBB conditions. In the present study, we attempted to identify major clinical determinants to predict CAD occurrence in patients with LBBB. Methods: A retrospective chart review of 229 consecutive patients with the diagnosis of complete LBBB pattern on electrocardiograms was conducted. The final diagnosis of LBBB was based on the Criteria Committee of the New York Heart Association. The participants were also classified based on coronary angiography evidences into two groups including CAD patients (n =99) and non-CAD patients (n =130). Results: Among 99 patients with CAD, 27 (27.3%) had single vessel disease, 30 (30.3%) had two-vessel disease and 42 (42.4%) had three-vessel disease. Also, only two of them had left main lesions. The number of diseased coronary vessels was significantly higher in men than in women so that three vessels disease in men was revealed in 28% and in women was observed in 10.9% (p = 0.002). Using a multivariable logistic regression analysis, male gender (2.445, 95% CI: 1.372-4.367, p = 0.002), advanced age (1.063, 95% CI: 1.032-1.095, p < 0.001), and cigarette smoking (4.112, 95% CI: 1.145-8.635, p = 0.012) were main predictors of CAD in LBBB patients. Conclusion: A notable number of patients with LBBB suffered concomitantly from CAD that the presence and severity of this ischemic event could be predicted by male gender, advanced age, and history of smoking in these patients.